Amorphous Carbon Films In Situ Formed From PTFE Transfer Layer in Solid Lubricated Cryogenic Turbopump Bearings. Issue 4 (4th July 2019) - Hu, Ming; Gao, Xiaoming; Wang, Peng; Fu, Yanlong; Sun, Jiayi; Weng, Lijun; Jiang, Dong; Wang, Desheng
Abstract: In order to fully evaluate the service reliability of cryogenic turbopump bearings, a newly developed solid lubricated bearing was tested using a custom ground bearing test system cooled by water. Stains with different color intensity were occasionally exhibited on the surfaces of the bearing balls after ground tests. This may pose a risk for the reliable service of the related bearings in real flight missions. Then the chemical composition and structural information of the stain layers were systematically analyzed by x-ray photoelectron spectroscopy (XPS), Raman spectroscopy, and high-resolution transmission electron microscope (HRTEM). The results manifested that the stain layer had the characteristic of α-C film. The color intensity of stains was not caused by the structural changes, but was due to the difference of stain layers' thickness. The α-C films in situ formed during bearings operation should result from the defluorination of polytetrafluoroethylene (PTFE) layers, which transferred from retainer to balls in the previous step. Correspondingly, FeF2 was produced on the surfaces of the tested bearing rings as a by-product. Although the tested bearings with α-C films formed on the surfaces of balls did not reach the state of final failure, the affected balls showed high surface roughness, which could be an indicator of an imminent bearing failure. Graphical Abstract: